Research Involvement among Undergraduate Health Profession Students in a Resource-Limited Setting: Awareness, Attitude, Motivators and Barriers - Kiyimba, Blaise; Atulinda, Linda; Nalunkuma, Racheal; Banturaki, Davis; Nabyonga, Anastacia Ssebbowa; Nkalubo, Jonathan (BMC Medical Education, 2022)
Involvement of undergraduate health professions students (HPS) in research will facilitate evidence-based clinical practice among future healthcare practitioners. This study aimed to assess research involvement among undergraduate HPS students and associated factors in Uganda. A cross-sectional study was conducted using an online assessment tool sent through WhatsApp groups and E-mail addresses of HPS in 12 medical schools in Uganda between 20th September and 5th October 2021. We enrolled 398 participants with a mean age of 23.9 ± 3.7 years. Of this, 267 (67.1%) were male. One hundred twenty (30.2%) participants previously participated in a research activity: 90 (58.4%) as research assistants, 39 (25.3%) published as first authors, and 25 (16.2%) as co-authors. Training on the conduct of research was received by 242 (65.8%) participants, and 326 (81.9%) had intentions of conducting research in the future. Factors influencing participation in research activities were, age ≥ 25 years (adjusted odds ratio (aOR): 1.9, 95% confidence interval (95% CI): 1.2–3.2, p = 0.012), being male (aOR: 2.1, 95%CI: 1.2–3.6, p = 0.008), and being in a clinical year i.e., year 3 (aOR: 3.2, 95% CI: 1.1–9.3, p = 0.033), year 4 (aOR: 3.3, 95% CI: 1.1–9.5, p = 0.028) and year 5(aOR: 11.6, 95% CI: 3.2–42.1, p < 0.001). Lack of funds (79.6%), and mentorship (63.3%) were reported as major barriers to research. Despite a high proportion of HPS showing interest in getting involved in research, less than one-third reported previous involvement. Addressing barriers such as funding could potentially improve research involvement and output among undergraduate HPS in resource-limited settings.
Keywords: Research; Undergraduate; Health; Students